Advocacy journalism and climate justice in a Global Southern country. Issue 4 (3rd April 2023) - Kamboh, Shafiq Ahmad; Ittefaq, Muhammad
ABSTRACT: Being among the world's most affected countries by climate change, Pakistan is facing a variety of cases of climate injustice committed by internal and external drivers. Waisbord's referred "Advocate-journalist" model carries a good potential to advocate these injustices to stimulate democratic dialogue among the audience that eventually pushes leadership to make eco-friendly policies. This study critically analyses advocacy journalism coverage of cases of local and regional climate injustice in the editorial contents of mainstream Pakistani newspapers by using the quantitative content analysis method. Results reveal that selected newspapers gave inappropriate coverage to climate injustice issues both in quantity and quality. Besides muddled local and regional climate injustice issues' priorities, editorialists also excessively recommended dirty energy solutions to the policymakers. The final analysis suggests that the findings of climate and energy-related scientific studies were not being reflected in the advocacy journalism contents as well. This failure of "advocate-journalist" model to perform its normative role of potentially advocating the cases of climate injustice with compelling scientific evidence seems to attribute to the political economy of the press or editorial inattention. As a way out of this journalistic lack, Waisbord's endorsed "civic advocacy" groups must intervene to plug the loopholes.